Cushing’s syndrome manifesting as chronic insomnia caused by adrenal cortical adenoma with incidental pituitary microadenoma: a case report - Rakhmayanti, Rizky; Minuljo, Tania Tedjo; Suryawati, Herlina; Fitrikasari, Alifiati; Soedarso, Mohamad Adi; Priambada, Dody (Journal of Biomedicine and Translational Research, 2021)
Background: Cushing’s syndrome is condition caused by excessive glucocorticoid with insomnia as one of its neuropsychiatric manifestation. Cushing’s syndrome may be caused by excessive adrenocorticotropin hormone (ACTH-dependent), for example from ACTH producing pituitary tumors, or by overproduction of cortisol by adrenocortical tumors. In this report, we presented a case with Cushing’s syndrome manifesting as chronic insomnia with adrenal cortical adenoma and pituitary microadenoma.Case presentation: A 30-year-old woman was consulted from the Neurologic Department to the Internal Medicine Department with the chief complaint of insomnia and worsening headache since 6 months prior to the admission. She had undergone head MRI and abdominal CT scan previously and was found to have both pituitary microadenoma and left adrenal mass. From the physical examination she had clinical signs of Cushing’s syndrome like Cushingoid face and purplish striae on her stomach. Midnight cortisol serum examination was done initially and showed high level of cortisol. High dose dexamethasone suppression test or DST (8 mg overnight) was later performed to help determine the main cause of Cushing’s syndrome. The result failed to reach 50% suppression of cortisol serum, suggestive that the Cushing’s syndrome was not ACTH-dependent from the pituitary but potentially from overproduction of cortisol by the left adrenal mass. Therefore, left adrenalectomy was performed and the histopathological study supported the diagnosis of adrenal cortical adenoma.Conclusion: Chronic insomnia is a very important symptoms of Cushing’s syndrome that should not be neglected. The patient had both microadenoma pituitary and left adrenal mass thus high dose DST test (8 mg overnight) needed to be performed to differentiate the source of Cushing’s syndrome. The result showed only little suppression therefore the pituitary microadenoma was not the source of Cushing’s syndrome and more suggestive from the adrenal etiology.